The Emerald handbook of childhood and youth in Asian societies : generations between local and global dynamics - Bühler-Niederberger, Doris; Gu, Xiaorong; Schwittek, Jessica; Kim, Elena (Emerald Publishing Limited, 2023)
The ebook edition of this title is Open Access and freely available to read online. More than half of the world's children grow up in Asia, a continent currently undergoing rapid economic and social change. Yet the voices of young people in Asian countries have received far too little attention. Providing a much-needed contribution to the field of childhood studies, The Emerald Handbook of Childhood and Youth in Asian Societies sets a new agenda in a research landscape that has so far lacked an overarching conceptual framework for illuminating Asian childhoods. Adopting a systematic and comprehensive approach, this pioneering handbook profiles Asian childhoods and youth embedded within their distinctive families and societies as well as in more universal contexts. Locating young people in a variety of social structures, chapters highlight and interrogate strong intergenerational obligations across Asian cultures, even as Asian societies undergo rapid economic change, political transformation, and mass migration. Prioritising Asian youth's perspectives and contributions and revising established analytical frameworks of research, The Emerald Handbook of Childhood and Youth in Asian Societies equips readers with an understanding of the complex interplay between local and global conditions and private and public actors in Asian countries.